The Impact of Technology and Social Media on Discrimination and Harassment in the Workplace - Dian Elyda Sarie; Silvani Yuzarni (Journal Discrimination and Injustice, 2025)
The development of technology and social media has brought significant changes in the dynamics of communication in the workplace. This study aims to answer two main questions: How do technology and social media affect discrimination and harassment in the workplace? and What is the impact of these practices on women? Using a descriptive qualitative method with a case study approach, this study focuses on the experiences of three female informants in the retail, digital services, and administration sectors in Lampung Province. Data were obtained through in-depth interviews, limited observations, and digital document analysis, which were analyzed using thematic techniques and a normative approach based on Mubādalah, a progressive Islamic perspective that emphasizes gender equality and justice. The results of the study show that technology and social media have become new channels for gender-based harassment and discrimination in the workplace. The forms include suggestive messages from superiors, sexist comments in work groups, and uploading photos without permission. The institutional response is generally passive and tends to blame the victim. The Mubādalah approach provides a normative alternative that emphasizes the need for corporate digital ethics reform with the principles of equality and collective protection. This study recommends the integration of Mubādalah values ​​in digital work policies to create a fair, safe, and inclusive work environment, especially for women